Lead Levels in Hair and Blood of Container Truck Drivers at PT. Trans Indo Sakti Surabaya - Juliana Christyaningsih; Amiliya Antika Dewi; Ayu Puspitasari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Lead is one of the heavy metals used as an additive in gasoline to enhance lubrication and combustion efficiency in motor vehicles, such as container truck drivers, and is commonly found on highways. Truck drivers have a higher tendency to inhale air containing lead while on the road, which can lead to poisoning. Hair and blood can serve as biomarkers of lead exposure in the body. The purpose of this research is to determine the lead levels in the hair and blood of container truck drivers at PT. Trans Indo Sakti Surabaya using Atomic Absorption Spectrophotometry (AAS). This research is a descriptive study conducted at the Analytical Chemistry Laboratory of the Department of Medical Laboratory Technology, Health Polytechnic Ministry of Health Surabaya and the Standardization and Industrial Services Center Laboratory in Surabaya from October 2022 to May 2023. The samples used in the study are 15 container truck drivers, selected using purposive sampling technique. This study demonstrates results of the lowest hair lead level value at 0.1936 µg/g and the highest at 3.026 µg/g. Among the respondents, 9 were categorized as having normal levels, while 6 respondents were categorized as having abnormal levels. For the blood samples, the lowest lead level obtained was 0.146 µg/dL and the highest was 3.81 µg/dL. The lead levels are still categorized as normal. The presence of lead in the body is influenced by age, length of employment, duration of work, and smoking habits.